Causes and outcome predictors of traumatic brain injury among emergency admitted pediatric patients at Cairo University Hospitals. Issue 4 (December 2015) - Youssef, Meray Rene L.; Galal, Yasmine S.
Abstract : Background: Traumatic brain injury (TBI) is a major global public health problem with significant morbidity and mortality, especially among the pediatric age group. Researchers are eager to find new diagnostic tools that might be useful for outcome prediction of pediatric TBI. Objective: This study aims to determine the causes of TBI in pediatric patients admitted to the Emergency Hospital at Cairo University, and monitor and evaluate some clinical and laboratory markers for outcome prediction. Patients and methods: A hospital-based prospective study was carried out; all pediatric patients with TBI admitted to the New Emergency Hospital during 6 months (November 2014–April 2015) were enrolled in the study. A total of 67 pediatric patients with TBI were examined and investigated upon admission and followed prospectively till discharge or death. Probing questions were used to collect data on child abuse and neglect. The Glasgow Coma Scale (GCS) was used for clinical assessment, followed by cerebral tomography (computed tomography scan). Routine laboratory investigations, arterial blood gases (pH, PCO2, and HCO3 ), and coagulopathy tests (prothrombin time, prothrombin concentration, international normalized ratio, and D-dimer) were performed on days 1 and 7. Results: Fall from height, traffic accidents, and direct head trauma represented 38.8, 34.3, and 21% of head trauma etiologies, respectively. Child neglect and abuse was detected in 62.7 and 18% of patients, respectively. Values of GCS at days 1 and 7 were significantly higher among survivors ( P <0.001). D-dimer levels on days 1 and 7 were significantly higher among nonsurvivors ( P <0.001). Receiver operating characteristics curve analysis showed the discriminative ability of D-dimer level on day 1 in predicting mortality with 89.3% sensitivity and 76.9% specificity. Conclusion and recommendations: Falls, traffic accidents, and direct head trauma were the most frequent etiologies for TBI in emergency admitted pediatric patients. Child neglect and abuse were the most prominent predisposing factors. GCS and D-dimer were the most important clinical and laboratory markers predicting mortality. Further large-scale studies are needed to determine the prevalence of TBIs and to prove the prognostic role of the D-dimer.